Bildung beyond the borders: racial ambiguity and subjectivity in three post-apartheid bildungsromane - Gamedze, Londiwe Hannah (Department of English Language and Literature, 2020)
This dissertation examines the subject formation of racially ambiguous protagonists in K Sello Duiker’s Thirteen Cents, (2001), Yewande Omotoso’s Bom Boy (2011) and Zoe Wicomb’s Playing in the Light (2006), three Bildungsromane set in post-apartheid Cape Town—the mother city—whose violent, racist histories of colonial encounters, slavery and apartheid have led to a strong social sense of racial group belonging and racial exclusion. It is between and among these strictly policed racial groups that these novels’ protagonists seek belonging and a place in society from which to act and speak. Although different aspects of racial ambiguity are foregrounded in these novels—namely phenotypical, cultural and political—these protagonists are all socially marginalised and they must form their identities and subjectivities at the intersections of social trauma and personal trauma brought about and catalyzed by the racist history and current socio-cultural formations in South Africa. Across the two socioscapes of society and family, this trauma is manifest as a gap in language—there is no affirming or cogent racial subject position for these figures from which to speak—and at the level of the body, where circulations of feeling produce the racially ambiguous body as abject or non-existent. As a sub-genre, the post-colonial Bildungsroman has been widely appraised as reconfiguring the thematic, structural and narrative traditions of its classical European counterpart, and my dissertation argues that these novels support this understanding. I also claim that they trace their racially ambiguous protagonists’ subject formation not from an initial subject position of self-centered, willful childhood innocence and ignorance but from a state of non-subjectivity into existence itself—proposing that the trajectories of the novels trace an ontological rather than ideological shift.